Emotion Regulation During Hostile Interactions: Optimizing Regulation Profiles for Event Performance and Well-Being - Melloy, Robert C.; Sayre, Gordon M.; Grandey, Alicia A. (Journal of Management, 2026)
When employees face hostility from others, emotion regulation is needed to perform effectively but can be personally costly. On the basis of current evidence, employees both perform better and avoid well-being costs with engagement-focused regulation (i.e., modifying feelings through deep acting) rather than with disengagement (i.e., modifying or faking expressions through surface acting). Yet, emotion regulation theorizing suggests this good–bad dichotomy is an oversimplification, and no known work has simultaneously considered the performance and well-being consequences of emotion regulation strategies at the event level. To address these issues, we apply the comprehensive six-strategy emotion regulation framework to identify emergent combinations of regulation strategies used in response to hostile events. Across two studies, we find six emotion regulation profiles, with the pattern of these profiles largely replicating across samples. Study 2 reveals that profile enactment is driven by the intensity of the event and has distinct consequences for employees’ event performance and well-being. We also find the first known evidence of a trade-off, where profiles that result in the highest negative affect were also the most effective for episodic performance. Meanwhile, profiles that maintained low levels of negative affect were linked with lower event performance ratings. Thus, in contrast to the good-bad strategy dichotomy common in the emotion regulation literature, we find that enhancing event performance comes at a cost to affect, and vice versa. This high-hostility work context points to a no-win situation for employees, who must choose between maximizing event performance and minimizing personal costs.